Determination of Vitamin C and ß-Carotene Levels in Several Types of Chili (Capsicum sp) Using UV-Vis Spectrophotometry Method - Annisa Febrianti; Ganea Qorry Aina; Eka Farpina (PT FORMOSA CENDEKIA GLOBAL, 2022)
Chili is a type of food that is rich in nutrition. There are quite a number of types of chili on the market, but in this study samples of red peppers, yellow peppers, green peppers, red shypoon chili peppers, and green santika chili peppers were used which had not been studied before using the UV-Vis spectrophotometry method. The purpose of this study was to describe the levels of vitamin C and β-carotene in several types of chili (Capsicum sp). This type of research is descriptive. The samples studied were 5 samples with the UV-Vis Spectrophotometry method. The data analysis used was Univariate analysis. The results showed that all samples contained levels of vitamin C and β-carotene with the results of vitamin C levels: red peppers (13.206 mg/g), yellow peppers (11.164 mg/g), red shypoon chili peppers (8.668 mg/g), paprika green chili (4.422 mg/g), green santika cayenne pepper (1.568 mg/g), β-carotene levels: red shypoon cayenne pepper (2.13 mg/g), yellow bell pepper (1.91 mg/g), paprika red (1.16 mg/g), green peppers (0.44 mg/g), green santika cayenne pepper (0.32 mg/g).